Effect of strategic memory advanced reasoning training (SMART) therapy for enhancing final-year high school students career choices - Amir Mahmood; Nadia Rehman; Xiao Huang; Noushin Zamani (BMC Psychology)
Abstract The SMART program improves students’ memory, reasoning, and strategic thinking skills, crucial for academic success and career planning. This study explored the effect of Strategic Memory Advanced Reasoning Training (SMART) for final-year high school students, aiming to enhance their decision-making abilities and prepare them for University. Based on the literature, nine hypotheses were developed with SMART program implementation therapy as an independent variable with four sub-variables: cognitive skills, professional development, social skills, and academic skills, and their impact on the dependent variable, such as career decision-making. Using a smart partial least square-structural equation modeling (PLS-SEM) on 284 high school students, confirmatory factor analysis (CFA) and structural equation modeling (SEM) was implemented to confirm the measurement model. Path analysis was conducted to determine the relationship between independent and dependent variables. Results of the study revealed that SMART therapy significantly enhances cognitive abilities, academic performance, personal development, and social skills, collectively contributing to better career decision-making among final-year high school students. However, the direct impact of SMART on career decision-making was not supported, indicating that additional factors, such as social and emotional influences, play a role. These findings suggest that integrating SMART therapy into high school curricula can better prepare students for future challenges and career opportunities, aligning with Sustainable Development Goal 4 (Quality Education). A collaborative approach among stakeholders, policy support, and innovative practices are recommended to overcome potential obstacles and ensure the successful implementation of SMART therapy in educational settings.